Are inflation, exchange rates and oil prices affect Air Asia stock return performance? / Nor Ashrina Mohd Jani - Mohd Jani, Nor Ashrina (2008)
The purpose of this study is to see whether inflation, exchange rates and oil prices are affect Air Asia stock return performance. The data are collected from year 2005 to 2007 on monthly basis. Air Asia stock return is used as dependent variable where by inflation, exchange rates and oil prices are used as independent variables. In order to test whether independent variables are affect dependent variables, Multiple Linear regression is used. Overall, the findings indicated whether there is significant effect between dependent and independent variables. According to the analysis for the year 2005 to 2007, which based on Multiple Linear Regression found that, exchange rates and inflation are not significantly influence the Air Asia stock return. However, oil prices are significantly influence Air Asia stock return at 10% significant level. As conclusion the results show that hypothesis 1 have been rejected due to it significant level with Air Asia stock return. While hypothesis 2 and 3 are accepted as they are not statistically significant to Air Asia stock return.